Rapid preparation process of novel nano material

FePSe3/C nanosheets were prepared by high purity treatment and gradient heating combined with mechanical ball milling, which solved the problem of low energy consumption of FePSe3 synthesis efficiency and high efficiency and low cost application of oxygen evolution reaction catalyst.

CN120398011APending Publication Date: 2025-08-01UESTC (SHENZHEN) ADVANCED RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510540469.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing FePSe3 nanomaterial synthesis method is low efficiency and high energy consumption, resulting in high cost and insufficient stability of the catalyst, making it difficult to apply to oxygen evolution reactions.

Method used

By performing high-purity treatment of iron source, red phosphorus and selenium powder, FePSe3 nanomaterial was prepared by gradient heating and mechanical ball milling method to form FePSe3/C nanosheet composite material to improve conductivity and catalytic activity.

Benefits of technology

It significantly reduces the overpotential of the oxygen evolution reaction, improves the preparation efficiency, reduces energy consumption and equipment costs, and realizes the efficient application of FePSe3 in the oxygen evolution reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398011A_ABST
    Figure CN120398011A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid preparation process of a novel nano material. The rapid preparation process comprises the following steps: step 1, pretreating raw materials; 2, mixing and pipe sealing; step 3, gradient temperature rise; the preparation method has the advantages that by optimizing the raw material combination, the reaction time is greatly shortened, the preparation efficiency is remarkably improved, meanwhile, the conductivity of FePSe3 is greatly improved through introduced carbon doping, the overpotential of the oxygen evolution reaction is successfully reduced to 524 mV at 100 mAcm <-2 > and is reduced by 23% compared with pure FePSe3 (677 mV), and the material can be used for preparing the high-current-density composite material under the industrial-grade high-current density, such as gt; the overpotential growth rate of 100mAcm <-2 > is remarkably lower than that of pure FePSe3, the energy consumption and equipment cost of hydrogen production by electrolysis of water can be greatly reduced, efficient synthesis of FePSe3 and innovative application of FePSe3 in OER are realized through raw material optimization and process improvement, the method has remarkable technical progress and commercial value, and the method is simple in process, low in energy consumption and suitable for industrial production. And a new way is provided for large-scale preparation of the high-performance OER catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic material preparation, and particularly relates to a rapid preparation process for a novel nanomaterial. Background Art

[0002] The oxygen evolution reaction, also known as Oxygen Evolution Reaction, abbreviated as OER, refers to the chemical reaction in which hydroxide ions or water lose electrons during electrolysis to generate oxygen. This reaction mainly occurs in the cathode region of the electrolytic cell.

[0003] The oxygen evolution reaction is a key reaction for hydrogen production by electrolyzing water. However, the existing catalysts are costly and lack stability. As a layered metal chalcogenide, FePSe3 has attracted much attention in the field of energy storage and conversion in recent years due to its unique electronic structure and catalytic activity. Although FePSe3 has potential catalytic activity, its low conductivity and slow synthesis process limit its application. The traditional synthesis method uses iron powder, red phosphorus, and selenium powder to prepare through solid-state reaction, which requires long-time firing at high temperature, with low efficiency and high energy consumption. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a rapid preparation process for a novel nanomaterial with high efficiency and low cost.

[0005] To solve the above technical problem, the present invention is solved by the following technical solutions: A rapid preparation process for a novel nanomaterial, comprising the following steps:

[0006] Step 1, raw material pretreatment: Further purify the iron source, red phosphorus, and selenium powder. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials;

[0007] Step 2, mixing and sealing the tube: Weigh the iron source, phosphorus source, and selenium source according to the stoichiometric ratio, mix them evenly, then put the raw materials into a quartz tube and evacuate it to less than or equal to 3×10 -3 Pa, and seal it;

[0008] Step 3, gradient heating: Place the sealed quartz tube in a muffle furnace, first heat it at a rate of 0.5 °C / min to 300 °C, keep it warm for 2 hours, then heat it at a rate of 1 °C / min to 650 °C, keep it warm for a period of time, and then naturally cool it to room temperature;

[0009] Step 4, nanometerization treatment: Put the cooled bulk material into a mechanical ball mill, add grinding media, and perform ball milling at a certain rotation speed and time to further grind the bulk into nanoscale powder to obtain FePSe3 nanomaterial.

[0010] Preferably, the iron source is ferrocene or iron powder, the purity of the red phosphorus is greater than or equal to 99.9%, and the purity of the selenium powder is greater than or equal to 99.9%.

[0011] Preferably, the mixing ratio of the iron source, red phosphorus and selenium powder is Fe:P:Se = 1:1:3.

[0012] Preferably, when the iron source is ferrocene, the heat preservation time is 1 day, and when the iron source is iron powder, the heat preservation time is 6 days.

[0013] Preferably, the inner diameter of the quartz tube is 10 mm, the wall thickness is 1-2 mm, and the length is 150 mm.

[0014] Preferably, the quartz tube is sealed with a hydrogen-oxygen flame, and the vacuum degree before sealing is less than or equal to -3 -3 3×10

[0015] Preferably, the grinding medium is agate balls and absolute ethanol.

[0016] Preferably, when the iron source is ferrocene, the carbon element generated by the pyrolysis of ferrocene is in-situ coated on the surface of FePSe3 to form a FePSe3 / C nanosheet composite material, and the thickness of the carbon layer is 3-8 nm.

[0017] Preferably, the application of FePSe3 nanomaterials in the electrocatalytic oxygen evolution reaction is suitable for alkaline water electrolysis hydrogen production systems.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The rapid preparation process of this novel nanomaterial, by optimizing the raw material combination, not only greatly shortens the reaction time and significantly improves the preparation efficiency, but also the introduced carbon doping greatly improves the conductivity of FePSe3, and successfully reduces the overpotential of the oxygen evolution reaction to 524 mV@100 mA cm -2 , a 23% decrease compared to pure FePSe3 (677 mV). At industrial-level high current densities, such as >100 mA cm -2 , the overpotential growth rate of this material is significantly lower than that of pure FePSe3, which can greatly reduce the energy consumption and equipment cost of water electrolysis hydrogen production. Through raw material optimization and process improvement, the present invention realizes the efficient synthesis of FePSe3 and its innovative application in OER, with significant technological progress and commercial value. This method has a simple process and low energy consumption, providing a new way for the large-scale preparation of high-performance OER catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention.

[0020] Figure 1 X-ray diffraction patterns of all materials in the examples;

[0021] Figure 2 Transmission electron microscopy images and energy-dispersive spectroscopy maps of the material obtained in Example 2;

[0022] Figure 3 Electrochemical OER polarization curves of all materials in the examples. Detailed implementation manners

[0023] Unless otherwise clearly specified in the context, nouns without a quantifier and nouns modified by "the" include singular and plural referents.

[0024] As used in the specification and claims, the terms "comprising", "including", "having", "can", "containing" and their variants refer to open transitional phrases, terms or words that require the presence of the specified component / step and allow the presence of other components / steps. However, such descriptions should also be construed as describing the composition or method as "consisting of" and "consisting essentially of" the recited components / steps, which allows only the presence of the specified components / steps and any inevitable impurities that may result therefrom, and excludes other components / steps.

[0025] The numerical values in the specification and claims of this application should be understood to include the same numerical values when reduced to the same number of significant figures and numerical values that differ from the said value by less than the experimental error of the conventional measurement techniques used to determine the said value in the type described in this application.

[0026] All ranges disclosed herein include the indicated endpoints and can be combined independently (e.g., the range of "2 grams to 10 grams" includes the endpoints 2 grams and 10 grams, and all intermediate values).

[0027] The terms "about" and "approximate" can be used to include any numerical value that can vary without changing the basic function of the value. When used with a range, "about" and "approximate" also disclose the range defined by the absolute values of the two endpoints. For example, "about 2 to about 4" also discloses the range of "2 to 4". Generally, the terms "about" and "approximate" can refer to ±10% of the indicated number. However, for temperature, the term "about" means ±1 °C.

[0028] Unless otherwise clearly specified, the percentage of an element should be considered as the weight percentage of the said alloy.

[0029] This disclosure may relate to the temperature of certain method steps. It should be noted that these indicators generally refer to the temperature set by a heat source (such as a furnace), rather than necessarily the temperature that the heated material must reach.

[0030] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments in the following description are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be used in other embodiments, variations, improvements, equivalent solutions, and other technical solutions without departing from the spirit and scope of the present invention.

[0031] The present invention provides a rapid preparation process for a new type of nanomaterial, comprising the following steps:

[0032] Step 1: Raw material pretreatment:

[0033] The iron source, such as ferrocene or iron powder, red phosphorus with a purity of greater than or equal to 99.9%, and selenium powder with a purity of greater than or equal to 99.5% are further purified. The chemical precipitation method is used to remove trace impurities in the iron source, the sublimation method is used to refine red phosphorus, and the distillation method is used to purify selenium powder to ensure the high purity of the raw materials;

[0034] Step 2: Mixing and sealing the tube:

[0035] Weigh the iron source, phosphorus source, and selenium source according to the stoichiometric ratio. Mix the iron source, red phosphorus, and selenium powder in a molar ratio of Fe:P:Se = 1:1:3. After mixing evenly, load the raw materials into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1 - 2 mm, and a length of 150 mm. Connect the vacuum system to evacuate to less than or equal to 3×10 -3 Pa, and use a hydrogen-oxygen flame to seal the tube mouth to ensure tightness. The vacuum degree before sealing the tube is less than or equal to 3×10 -3 Pa;

[0036] Step 3: Gradient heating:

[0037] Place the sealed quartz tube in a muffle furnace. First, heat it at a rate of 0.5 °C / min to 300 °C and hold for 2 hours. Then, heat it at a rate of 1 °C / min to 650 °C and hold for a period of time. Subsequently, cool it naturally to room temperature. When the iron source is ferrocene, the holding time is 1 day, and when the iron source is iron powder, the holding time is 6 days. When the iron source is ferrocene, the carbon element generated by the pyrolysis of ferrocene is in-situ coated on the surface of FePSe3 to form a FePSe3 / C nanosheet composite material, and the thickness of the carbon layer is 3 - 8 nm;

[0038] Step 4: Nanometerization treatment:

[0039] Put the cooled bulk material into a mechanical ball mill, add grinding media. The grinding media are agate balls and absolute ethanol. Carry out ball milling at a certain rotation speed and time to further grind the bulk material into nanoscale powder to obtain FePSe3 nanomaterial.

[0040] The specific steps are as follows: Further purify the iron source, such as ferrocene or iron powder, red phosphorus with a purity of greater than or equal to 99.9%, and selenium powder with a purity of greater than or equal to 99.5%. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials. Weigh the iron source, phosphorus source, and selenium source according to the stoichiometric ratio, and mix ferrocene, red phosphorus, and selenium powder in a molar ratio of Fe:P:Se = 1:1:3. After mixing evenly, load the raw materials into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1 - 2 mm, and a length of 150 mm, connect the vacuum system to evacuate to less than or equal to 3×10 -3 Pa, and use a hydrogen-oxygen flame to seal the tube mouth to ensure airtightness. The vacuum degree before sealing the tube is less than or equal to 3×10 -3 Pa. Gradually increase the temperature: Place the sealed quartz tube in a muffle furnace, first heat it to 300 °C at a rate of 0.5 °C / min and hold for 2 hours, then heat it to 650 °C at a rate of 1 °C / min and hold for a period of time, and then naturally cool to room temperature. When the iron source is ferrocene, the holding time is 1 day, and when the iron source is iron powder, the holding time is 6 days. When the iron source is ferrocene, the carbon element generated by the pyrolysis of ferrocene is in-situ coated on the surface of FePSe3 to form a FePSe3 / C nanosheet composite material, and the carbon layer thickness is 3 - 8 nm. Nanometrization treatment: Put the cooled bulk material into a mechanical ball mill, add grinding media, and the grinding media is agate balls and absolute ethanol. Carry out ball milling at a certain rotation speed and time to further grind the bulk into nanoscale powder to obtain FePSe3 nanomaterial.

[0041] Example 1. A rapid preparation process for a new type of nanomaterial, including the following steps:

[0042] Step 1. Pretreatment of raw materials:

[0043] Further purify iron powder, red phosphorus with a purity of greater than or equal to 99.9%, and selenium powder with a purity of greater than or equal to 99.5%. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials;

[0044] Step 2. Mixing and sealing the tube:

[0045] Weigh 10 mmol of iron powder, 10 mmol of red phosphorus, and 30 mmol of selenium powder according to the stoichiometric ratio, and mix and grind the iron powder, red phosphorus, and selenium powder in a molar ratio of 1:1:3 in an argon glove box for 30 minutes until evenly mixed; Load the precursor powder into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1.5 mm, and a length of 150 mm, connect the vacuum system to evacuate to 3×10 -3 Pa and then seal the tube mouth with a hydrogen-oxygen flame;

[0046] Step 3. Gradually increase the temperature:

[0047] Place the sealed quartz tube in a muffle furnace. First, heat it at a rate of 0.5 °C / min to 300 °C and hold for 2 hours. Then, heat it at a rate of 1 °C / min to 650 °C and calcine for 6 days. Subsequently, cool it naturally to room temperature.

[0048] Step 4: Nanostructuring treatment:

[0049] After natural cooling, break the quartz tube to obtain a bulk material. Put the cooled bulk material into a mechanical ball mill, add agate balls and absolute ethanol as grinding media, and perform ball milling at a certain rotation speed and time to further grind the bulk into a nano-scale powder. After washing with ethanol and drying, the target product FePSe3 is obtained.

[0050] The specific steps are as follows: Further purify iron powder, red phosphorus with a purity of greater than or equal to 99.9%, and selenium powder with a purity of greater than or equal to 99.5%. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials. Weigh 10 mmol of iron powder, 10 mmol of red phosphorus, and 30 mmol of selenium powder according to the stoichiometric ratio. Mix and grind the iron powder, red phosphorus, and selenium powder in an argon glove box at a molar ratio of 1:1:3 for 30 minutes until uniform. Load the precursor powder into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1.5 mm, and a length of 150 mm. Connect the vacuum system and evacuate to 3×10 -3 Pa, then seal the tube mouth with a hydrogen-oxygen flame. Place the sealed quartz tube in a muffle furnace. First, heat it at a rate of 0.5 °C / min to 300 °C and hold for 2 hours. Then, heat it at a rate of 1 °C / min to 650 °C and calcine for 6 days. Subsequently, cool it naturally to room temperature. After natural cooling, break the quartz tube to obtain a bulk material. Put the cooled bulk material into a mechanical ball mill, add agate balls and absolute ethanol as grinding media, and perform ball milling at a certain rotation speed and time to further grind the bulk into a nano-scale powder. After washing with ethanol and drying, the target product FePSe3 is obtained. As Figure 1 shown, the material prepared in Example 1 can be completely matched with the standard PDF card, indicating that pure-phase FePSe3 is obtained. Figure 2 The TEM characterization of a also confirms that the sample in Example 1 has good crystallinity. Under a three-electrode system, using 1 mol / L potassium hydroxide solution as the electrolyte, Hg / HgO as the reference electrode, a graphite rod as the counter electrode, and a carbon paper loaded with FePSe3 as the working electrode, test its electrochemical OER performance as Figure 3 shown. In 1 M KOH, the overpotential of FePS3 at 100 mA cm -2 is 677 mV.

[0051] Example 2. A rapid preparation process of a new type of nanomaterial, comprising the following steps:

[0052] Step 1. Raw material pretreatment:

[0053] Perform further purification on ferrocene, red phosphorus with a purity of not less than 99.9%, and selenium powder with a purity of not less than 99.5%. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials;

[0054] Step 2. Mixing and sealing the tube:

[0055] Weigh 10 mmol of ferrocene, 10 mmol of red phosphorus, and 30 mmol of selenium powder according to the stoichiometric ratio. Mix and grind ferrocene, red phosphorus, and selenium powder in an argon glove box at a molar ratio of 1:1:3 for 30 minutes until homogeneous. Load the precursor powder into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1.5 mm, and a length of 150 mm. Connect the vacuum system and evacuate to 3×10 -3 Pa, and then seal the tube mouth with a hydrogen-oxygen flame;

[0056] Step 3. Gradient heating:

[0057] Place the sealed quartz tube in a muffle furnace. First, heat it at a rate of 0.5 °C / min to 300 °C and hold for 2 hours. Then, heat it at a rate of 1 °C / min to 650 °C and calcine for 1 day, and then naturally cool it to room temperature;

[0058] Step 4. Nanostructuring treatment:

[0059] After natural cooling, break the quartz tube, collect the black powder, wash it with ethanol and dry it to obtain the target product FePSe3 / C.

[0060] The specific steps are as follows: Perform further purification on ferrocene, red phosphorus with a purity of not less than 99.9%, and selenium powder with a purity of not less than 99.5%. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials. Weigh 10 mmol of ferrocene, 10 mmol of red phosphorus, and 30 mmol of selenium powder according to the stoichiometric ratio. Mix and grind ferrocene, red phosphorus, and selenium powder in an argon glove box at a molar ratio of 1:1:3 for 30 minutes until homogeneous. Load the precursor powder into a quartz tube with an inner diameter of 10 mm, a wall thickness of 1.5 mm, and a length of 150 mm. Connect the vacuum system and evacuate to 3×10 -3After Pa, the tube opening was sealed with a hydrogen-oxygen flame. The sealed quartz tube was placed in a muffle furnace. First, it was heated to 300 °C at a rate of 0.5 °C / min and held for 2 hours. Then, it was heated to 650 °C at a rate of 1 °C / min and calcined for 1 day. Subsequently, it was naturally cooled to room temperature. After natural cooling, the quartz tube was broken, and the black powder was collected. After washing with ethanol and drying, the target product FePSe3 / C was obtained. As Figure 1 shown, the material prepared in Example 2 was a pure phase of FePSe3. Compared with Example 1, its diffraction peak intensity was weaker because the crystallinity decreased due to carbon doping. And after using ferrocene, the obtained product was in powder form and did not need to be ground again, and its crystal size was smaller. As Figure 2 shown in b, Example 2 had an ultrathin nanosheet structure, and there was an amorphous carbon layer about 5 nm on the surface of its sample, while Figure 2 the surface lattice fringes of Example 1 shown in a were continuous and the edges were sharp, and no amorphous covering layer was observed. It could be confirmed by the energy spectrum diagram that the C element was uniformly distributed on the surface of FePSe3. Under a three-electrode system, with 1 mol / L potassium hydroxide solution as the electrolyte, Hg / HgO as the reference electrode, a graphite rod as the counter electrode, and a carbon paper loaded with FePSe3 / C as the working electrode, its electrochemical performance was tested as Figure 3 shown, showing that its OER overpotential was 524 mV (100 mA cm -2 ), which was better than that of pure FePSe3 (677 mV). This indicated that the carbon coating layer effectively improved the electrochemical performance of FePSe3.

[0061] Those skilled in the art should understand that the embodiments of the present invention shown in the above description are only examples and do not limit the present invention. The object of the present invention has been fully and effectively achieved. The functions and structural principles of the present invention have been shown and described in the embodiments. Without departing from the said principles, the embodiments of the present invention can have any deformation or modification. Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents. This specific embodiment is only an interpretation of the present application and does not limit the present application. Those skilled in the art can make modifications without creative contributions to this embodiment according to needs after reading this specification, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. A rapid preparation process of a novel nanomaterial, characterized in that: It includes the following steps: Step 1, raw material pretreatment: Further purify the iron source, red phosphorus and selenium powder. Use the chemical precipitation method to remove trace impurities in the iron source, refine red phosphorus by the sublimation method, and purify selenium powder by the distillation method to ensure the high purity of the raw materials; Step 2, mixing and sealing the tube: Weigh the iron source, phosphorus source and selenium source according to the stoichiometric ratio. After mixing evenly, put the raw materials into a quartz tube and evacuate it to less than or equal to 3×10-3 Pa, and then seal it; Step 3, gradient heating: Place the sealed quartz tube in a muffle furnace. First, heat it at a rate of 0.5 °C / min to 300 °C and keep it warm for 2 hours. Then, heat it at a rate of 1 °C / min to 650 °C and keep it warm for a period of time. Subsequently, cool it naturally to room temperature; Step 4, nanosizing treatment: Put the cooled bulk material into a mechanical ball mill, add grinding media, and carry out ball milling at a certain rotation speed and time to further grind the bulk into nanoscale powder to obtain FePSe3 nanomaterial.

2. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: The iron source is ferrocene or iron powder, the purity of the red phosphorus is greater than or equal to 99.9%, and the purity of the selenium powder is greater than or equal to 99.9%.

3. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: The mixing ratio of the iron source, red phosphorus and selenium powder is Fe:P:Se = 1:1:

3.

4. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: When the iron source is ferrocene, the holding time is 1 day; when the iron source is iron powder, the holding time is 6 days.

5. A rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: The inner diameter of the quartz tube is 10 mm, the wall thickness is 1-2 mm, and the length is 150 mm.

6. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: The quartz tube is sealed at the tube mouth by using a hydrogen-oxygen flame. The vacuum degree before sealing the tube is less than or equal to 3×10 -3 Pa.

7. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: The grinding media is agate balls and absolute ethanol.

8. The rapid preparation process of a novel nanomaterial according to claim 1, characterized in that: When the iron source is ferrocene, the carbon element generated by the pyrolysis of ferrocene is in-situ coated on the surface of FePSe3 to form a FePSe3 / C nanosheet composite material, and the thickness of the carbon layer is 3-8 nm.

9. An FePSe3 nanomaterial prepared by the method according to any one of claims 1-8, characterized in that: The application of FePSe3 nanomaterial in the electrocatalytic oxygen evolution reaction is suitable for the alkaline electrolytic water hydrogen production system.